Mahabharat: retold with scientific evidence - Bala, Saroj (Gurugram Garuda Prakashan, 2021)
This book will compel the reader to look at the evidence and re-calibrate his understanding of ancient India. Specifically, if Mahabharat war was fought in 3139 BCE, are we not supposed to conclude that the Harappan Civilisation was actually the Vedic civilisation of Mahabharat era? The reader will be enthralled to look at the evidence of the Kali Era conjunction in the morning of 19th February 3102 BCE, heralding the beginning of Kaliyuga. Besides astronomy, the book puts forth evidence from seven disciplines of science. It proves the profound philosophy of Bhagavad Gita was actually passed on to the world on Shukla Ekadashi of Margashirsha Month in 3139 BCE. Most of the excavated sites, having carbon dates of samples and artefacts around 3000 BCE and associated with Harappan civilisation, were actually located within the territories of kingdoms which participated in Mahabharat war. Also, this book takes note of different claims made by esteemed scholars on the date of Mahabharat war, and establishes that the war took place in the year 3139 BCE, adding to the healthy discourse on the timing of Mahabharat war.The research for this book entailed detailed reading and interpretation of Mahabharat by Sanskrit scholars; getting exact sky-views through the software, calculating and adjusting for the changes in astronomical situations down thousands of years and re-visiting the findings to make them error-free.
Keywords: Religion-Hindu; Hinduism; Mahabharta; Author as a Civil Servant (IRS)